Televisions and Democracies: Mass Media and Web TV in Externado University of Colombia - Cardona del Real, Felipe (2013)
The understanding of democracy as a political organization form, has in many scenarios the debate on how pure is in a representative form and how effective is when is “pure” or direct democracy, as well as thought for the “polis” or places with an specific geographic location, contrary to the Saskia Sassen concept of “global cities”. From this discussion, we can address the television as a twentieth century mass media, funded and operated by governments or private companies, exercising symbolic power in a nation, as seen by the John B. Thompson power forms in modern societies, and as an organizational form that clearly exemplifies a representative democracy from the choice of themes, characters, speech and even workflow technology.